NZF Nanoscale Particles: Synthesis, Characterization and its Effective Adsorption of Bromophenol Blue - Benhadria Naceur; Elaziouti Abdelkader; Laouedj Nadjia; Sari Esmahene (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The ferrospinels NixZn1_xFe2O4 (x = 0.0 and 0.6) nanoparticles (NPs) were successfully prepared by a sol-gel method and analyzed by TGA/DTA, XRD, SEM-EDS, UV-Vis-DRS, and pHIEP. The adsorption potential of NZF NPs towards the Bromophenol blue (BPB) dye was investigated. The batch adsorption efficiency parameters were studied including contact time, pH, initial dye concentrations and catalyst dosage. Results indicated that NZF crystallized in single-phase and exhibited smaller crystallite size (49 nm vs. 59.24 nm) than that of the pristine (ZF). The SEM analysis showed that the materials are elongated-like shape. NZF catalyst showed a red-shift of absorption bands and a more narrowed band gap (2.30 eV vs. 1.65 eV) as compared to ZF. The adsorption process was found to be highly dependent to the pH of the solution, dye concentration and adsorbent dose. Under optimum conditions of 5 mg.L–1 BPB, 0.5 g.L–1 NZF catalyst, pH = 6, and 25 °C, up to ≈ 86.30% removal efficiency could be achieved after 60 min. Pseudo-second-order kinetic model gave the best fit with highest correlation coefficients (R2 ≥ 0.99). A high specific surface area, a stabilized dispersion state of NZF NPs and the electrostatic interaction between the BPB-2 anions and the NZF-H3O+active sites on NZF surface were believed to be the main factors that can be responsible for the high adsorption efficiency. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).